Selfhood, Place, and Ideology in German Photo Albums, 1933–1945 - Umbach, Maiken (Cambridge University Press, 2015)
This article explores the significance of photography and photo album making as practices through which many Germans recorded their lives during the ‘Third Reich’. Millions of photos not only offer us insights into everyday life under National Socialism: mass photography itself had a transformative effect, turning seemingly mundane actions into performances for the camera and conscious acts of self-representation. The article also considers the relationship between amateur snapshots and propagandistic and commercial photographs. Identifying connections between these genres, it argues that these are best understood as two-ways processes of borrowing and (re-) appropriation, in which private subjectivity and public ideology constantly commingled. Particularly important in linking the two were photos of emotional or affective states, such as relaxation, exploration, introspection, and even melancholy, which were often defined or underscored by the way in which both civilians and soldiers positioned themselves in relation to particular landscapes. The photographic archive is highly varied, but such variation notwithstanding, it helped cement immersive ‘experience’ as the basis for individual and collective identity, which was central to the ideology of the National Socialist regime, even if its meanings were never wholly controlled by it.